The adoption of multicurrency system a panacea to urban dwellers socio-economic challenges? perspectives of high density suburbs' residents in Gweru, Zimbabwe - Marambanyika, Thomas; Muziti, Trish-mae; Matsa, Mark; Mutekwa, Timothy (Clarion University of Pennsyslavia, 2016)
Zimbabwe experienced a crippling hyperinflationary economic environment, which created a nation of poverty-stricken billionaires over the past decade until it adopted the multicurrency system (MCS) in January 2009. The paper explores on the impact of the change in monetary regime on socio-economic conditions of urban dwellers, given their overreliance on the market economy and vulnerability to its fluctuations. Questionnaires, semi-structured interviews, and participatory observations were used targeting household heads, school heads, and sister in charge of the local clinic. The research found that although the multicurrency system has generally improved the quality of life for the majority of people, they still remain in poverty if one considers the quality of life indicators, like the national poverty datum line. There was great change in nature and patterns of sources of income, particularly for informal traders, a sector which had become the backbone of almost all households’ income in pre-MCS era. MCS brought with it the inherent problem of inadequacy and, in some cases, unavailability of smaller denominations. The government must adopt a single currency to avoid exchange rate problems, as well as reduce shortages of smaller denominations.